Pelatihan Penentuan Harga Pokok Penjualan Kue Mochi dengan Metode Full Costing - Fajar Kurnianto; Zaenal Wafa (Politeknik Piksi Ganesha Indonesia, 2024)
MSMEs are a business group with a large contribution as a provider of employment, a means of community empowerment, creating new markets, and contributing to gross domestic product. Almost 99 percent of business units in Indonesia are MSMEs and in 2024, especially in the Special Region of Yogyakarta, the number will increase compared to 2023. However, the increase in the quantity of MSME units is not accompanied by an increase in the quality of financial performance. Many MSME players sell products without knowing the cost of goods sold, even though this affects the formation of the selling price of the product. Therefore, this activity aims to provide education and training related to how to determine the right COGS using the full costing method. MSMEs who previously did not understand the accounting concept of determining COGS are expected to better understand and be able to apply the calculation of COGS, so that they can maximize profits while still considering the purchasing power of the community.